Vehicle control - Brinza, Andreea-Cornelia (Eximia, 2023)
Through the activities carried out, a police officer constantly seeks to protect life and the bodily integrity and other legitimate rights and interests of citizens. In this sense, the action to impose the law is fully justified and must be explained to those concerned, to make them understand that as long as they align with the established norms, they will not be subject to its repressive side. The activity of a traffic policeman is carried out in a planned manner, according to the daily activity plan and established patrol variants, which eliminates its random character. Traffic police activities are carried out by crews (patrols) made up of at least two traffic policemen. In special situations, when for objective reasons this configuration of the crew cannot be ensured, it is accepted that one of the policemen belongs to another police formation, or is replaced by a gendarme or by support persons. At the request of the traffic participant, a policeman presents himself with his service ID. If the citizen has doubts about the policeman’s presence in traffic in the place and at that time or if he is interested in whether he is in the exercise of his duties, he can contact the nearest police unit (municipal or city police, respectively police station) communal), the policeman being obliged to present the personal documents or the devices used only to the competent authorities.